1984
DOI: 10.1111/j.1528-1157.1984.tb04199.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Penetration of Common Antiepileptic Drugs into Cerebrospinal Fluid

Abstract: The rate of entry of common antiepileptic drugs and some active metabolites into cerebrospinal fluid (CSF) was studied in anesthetized dogs from which blood and CSF samples were withdrawn at short intervals. Diazepam, its active metabolites desmethyldiazepam and oxazepam, clonazepam, and ethosuximide entered the CSF very rapidly with mean half-times to equilibrium between 3 and 7 min. Valproic acid, phenytoin, phenobarbital, and carbamazepine went in more slowly, but mean penetration half-times were still only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 14 publications
(11 reference statements)
3
25
0
Order By: Relevance
“…4), the conversion of primidone to phenylethylmalonamide occurred earlier and also more rapidly than the conversion to phenobarbital. Thus, a rate-limiting formation of phenobarbital from primidone is suggested and confirms previous observations (34,35). Since this pattern pertains in the CSF compartment in addition, it might reasonably be concluded that, at least in the acute situation, the dosedependent anticonvulsant effect of primidone could be primarily attributable to primidone, but that phenylethylmalonamide and to a lesser extent phenobarbital also contribute (3,5,7).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…4), the conversion of primidone to phenylethylmalonamide occurred earlier and also more rapidly than the conversion to phenobarbital. Thus, a rate-limiting formation of phenobarbital from primidone is suggested and confirms previous observations (34,35). Since this pattern pertains in the CSF compartment in addition, it might reasonably be concluded that, at least in the acute situation, the dosedependent anticonvulsant effect of primidone could be primarily attributable to primidone, but that phenylethylmalonamide and to a lesser extent phenobarbital also contribute (3,5,7).…”
Section: Discussionsupporting
confidence: 78%
“…The fourth study, which was undertaken in three anaesthetised dogs (6), involved serial blood and CSF sampling after injection of a single dose of primidone and phenylethylmalonamide together directly into the jejunum. One study investigated the concurrent neuropharmacokinetics of primidone in brain (3) whilst Loscher and Frey (34) used an anaesthetised dog model and reported only on the entry of primidone and phenylethylmalonamide into the CSF compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The high aqueous solubility of HPPCD results in vastly improved solubility of numerous compounds, including CBZ (3,5,6). Because CBZ is nonionized at pH 7.4 and is highly lipid soluble, the drug rapidly penetrates the CNS at a rate similar to that of PHT (17). We therefore proposed that CBZ/HPPCD solutions should be ideally suited for parenteral administration to control severe epileptic attacks or SE (6), as was substantiated by the present study.…”
Section: Discussionsupporting
confidence: 53%
“…By studying the rate of entry of various AEDs from blood into the CSF of anesthetized dogs, Löscher and Frey (1984) found a significant correlation between penetration rate and lipid solubility, measured by organic solvent/buffer distribution ratios, whereas the extent of plasma protein binding and degree of ionization of AEDs were of minor importance for penetration rates. These data thus substantiated that lipid solubility plays the major role in determining the difference in rate of entry of AEDs, and that AEDs, as do most centrally active drugs, penetrate into the CSF by simple diffusion.…”
Section: Active Transport Of Antiepileptic Drugs In the Blood-brain Amentioning
confidence: 99%
“…Valproate, a branched medium-chain fatty acid, is almost completely ionized at physiologic pH, and its lipid solubility at this pH is therefore very low (Löscher and Frey, 1984). However, although it has been shown that drugs with such properties enter the CSF or brain very slowly if at all (Goldstein et al, 1974), valproate penetrated into the CSF and brain very rapidly (Löscher, 1982;Löscher and Frey, 1984). Indeed, valproate was the first AED for which an active transport in the BCB and BBB has been proposed (Frey and Löscher, 1978).…”
Section: Active Transport Of Antiepileptic Drugs In the Blood-brain Amentioning
confidence: 99%